The glorious adventure - Halliburton, Richard (The Bobbs-Merrill company, 1927)
Djerba p. 173-194
Keywords: Récits de voyage – Djerba

Sands, palms and minarets - Vernon, Madeleine (F.A. Stokes, 1927)
Keywords: Récits de voyage – Djerba

Vanished cities of Northern Africa - Erskine, Beatrice (Haughton Fletcher, 1927)
Keywords: Récits de voyage – Djerba